Ordbog over Dansk Talesprog (ODT) – værkstedspræsentation af en ordbogsportal - Hansen, Carsten; Hansen, Martin H. (Nordiske Studier i Leksikografi, 2012)
The article presents the initial investigating stages of the development of a dictionary of spoken Danish, based on a corpus consisting mainly of sociolinguistic interviews at the LANCHART Centre in Copenhagen. The data are stratified and represent different segments of Danish speakers with regard to geography, gender, age and social class, recorded over several decades. The purpose of the dictionary is to present spoken Danish to the interested layperson as well as the research-oriented user, and the dictionary will be designed as an online portal with these recipients in mind. The article presents several examples of work in progress: establishing the editing principles of linguistic fact boxes which will give a more detailed presentation of a specific topic; a sketch of the portal design; a pilot project on interjections with an, as yet, unfinished dictionary entry on the lemma av (‘ouch’); and finally, an investigation of laughter as part of spoken language which also demonstrates how the tagging of a sociolinguistic corpus can be put to use in a dictionary.